TNF Superfamily 2008 - Ware, Carl F. (2008)
This Special Edition of Cytokines and Growth Factor Reviews emerged from the most recent International TNF Conference, held May 13–16, 2007. The conference, organized by TNF aficionados, Avi Ashkenazi (Genentech, South San Francisco) and Jeffrey Browning (BiogenIDEC, Boston, MA), was held a second time in the serene coastal environs of the rustic Asilomar State Conference Center in Monterey, California. The scientific presentations at the Asilomar meeting kept pace with the previous 10 pseudo biennial TNF-related cytokine conferences, each heralding new discoveries about this important family of cytokines. Perhaps as a sign of the family’s maturing knowledge base, new results from clinical trials were revealed for members of the family other than TNF, such as TRAIL in cancer and Lymphotoxin-β in rheumatoid arthritis. The next meeting, the 12(th) International TNF Conference is scheduled for April 26–29, 2009 in El Escorial, Madrid, Spain, co-chaired by Marc Feldman and David Wallach (www.tnf2009.org).